Cucumber and tomato seedlings fortified with silicon and chlorine - Flores Cázarez Flores, Luz Llarely; Velázquez Alcaraz, Teresa de Jesús; Partida Ruvalcaba, Leopoldo; Ayala Tafoya, Felipe; Zazueta Torres, Norma Delia; Yáñez Juárez, Moisés Gilberto (Revista Mexicana de Ciencias Agrícolas, 2023)
The use of silicon (Si) and chlorine (Cl) allows plants to favorably increase growth and development, as they contribute to the increase in dry weight of plants and chlorophyll biosynthesis, as well as resistance to biotic and abiotic factors. The research was carried out to clarify the result caused by the application of Si and Cl in the growth of cucumber and tomato seedlings. For this, cucumber ‘Paraiso F1’ and tomato F3 were sown in polystyrene trays with 242 cavities filled with peat moss. The experimental design of randomized complete blocks was used, where the treatments were: 20, 30 and 50 mg L-1 of Si, 20, 30 and 50 mg L-1 of Cl, 20:20, 30:30 and 50:50 mg L-1 of Si:Cl, one absolute control and four repetitions per treatment. The response variables were leaf greenness, plant height, leaf area, dry weight of the aerial part and root in cucumber and tomato seedlings. In cucumber seedlings, leaf greenness increased by 18.7% and 4.6% with 20 and 50 mg L-1 of Si and Cl, respectively. The combination of 20:20 mg L-1 of Si:Cl increased the biomass of the aerial part by 30.2%. While, in tomato seedlings treated with 30 mg L-1 of Si and in mixture with Cl at concentration 30:30 mg L-1, their height was 31.9% and 25.1% with respect to the control seedlings. Dry root biomass was significantly increased with the application of Si (20 and 30 mg L-1), Cl (20 and 50 mg L-1) and in combination 30:30 (mg L-1).